Crystalline quality of GaAs1−xBix grown below 250 °C using molecular beam epitaxy. (1st April 2022) - Tominaga, Yoriko; Horita, Yukihiro; Takagaki, Yuto; Nishiyama, Fumitaka; Yukimune, Mitsuki; Ishikawa, Fumitaro
Abstract: This study revealed the crystalline quality of the dilute bismide alloy GaAs1− x Bi x grown on a GaAs(001) substrate below 250 °C using molecular beam epitaxy. The substrate temperature and As flux played a dominant role in tuning the crystal structure between amorphous and single crystalline GaAs1− x Bi x, as well as in the Bi introduction in GaAs below 250 °C. Sample characterization demonstrated a substrate temperature of 250 °C produced single crystalline ∼200 nm thick GaAs0.982 Bi0.018 with clear X-ray diffraction fringes, while the lower substrate temperature of 180 °C yielded an amorphous film. Rutherford backscattering spectrometry showed sufficient As supply at the growing surface provides uniform Bi distribution.